WE ARE FROM THE SAME ANCESTORS: CHRISTIAN-MUSLIM RELATIONS IN CONTEMPORAY ACEH SINGKIL - Muhammad Ansor (Al-Albab, 2014)
The following Paper discusses the Muslim-Christian relations in Aceh Singkil Regency as well as the process of religious identity formation in the context of the debate over the Islamic Sharia in Aceh. First of all I will present the overview of the socio-political context of the regulations of Islamic jurisprudence in Aceh and the position of non-Muslims in such regulations. Next, I will trace the impact of the regulations on the format of the Muslim-Christian relations. Based on the Goffman theory of dramaturgy, this paper found that Muslim-Christian relations in Singkil were a complex narrative, often opposite between the appearance of the front stageand the backstage. Amid suspicions of the majority of the Aceh Singkil Muslims and the local Government of the existence of Christians, Interfaith communities at the grassroots level are precisely trying to build harmony and co-existence. I conclude that the consciousness about the similarities of ethnic origins has so far contributed effectivelyto suppressing the conflict between the two religions in Aceh Singkil. Keywords: Ethnicity, Muslim-Christian Relations, Aceh Singkil